Characteristics and functional analysis of the secondary chromosome and plasmids in sphingomonad. (July 2022) - Song, Da; Chen, Xingjuan; Xu, Meiying
Abstract: Sphingomonads, an important bacterial group with metabolic versatility, are ubiquitous in polluted environments and show significant potentials in detoxification and bioremediation. Their genomes generally contain multiple plasmids and even a secondary chromosome (Chr2), on which there are abundant genes involved in xenobiotics degradation and environmental adaptation. This review analyzed the 109 available complete genomes of sphingomonads and outlined the related literature to describe the characteristics, namely sizes, copy numbers, maintenance systems, evolutionary processes and metabolic potentials of the Chr2s and plasmids. Some interesting findings and relationships are revealed. The copy numbers of small plasmids vary from approximately 0.1 to 7.1, while those of Chr2s and megaplasmids are closer to 1. The type of replication initiation protein (Rep) encoded by plasmid could affect the plasmid size. Chr2s may originate mainly from the megaplasmids encoding RPA-type Rep protein with the skeletons appearing prior to the species differentiation, and the events that Chr2s obtained 16S rRNA genes likely happened after the species formation. Although primary chromosomes, Chr2s and plasmids show different functional biases, they share massive gene families. This review provides insights into the evolution and adaptation of sphingomonads, and contributes to obtaining useful genes for biotechnology and guiding the applications of sphingomonads. Highlights: About 2/3 of the available complete genomes of sphingomonads are multipartite. The copy number and maintenance system of plasmid are related to its size. The secondary chromosomes may be mainly from the RPA-type megaplasmids. The chromosomes and plasmids show different functional biases. Significant genetic exchanges happen among different replicons.